Reunions : visionary encounters with departed loved ones - Moody, Raymond A.; Perry, Paul, 1950- (New York : Villard Books, 1993)
Offers clear evidence for the existence of life after death, detailed instructions on how to communicate with the dead, and a collection of accounts of the paranormal
Includes bibliographical references (p. 209-212) and index
Keywords: Spiritualism; Death; Visions